Perancangan Perangkat Lunak Kompresi Citra Menggunakan Transformasi Wavelet dan PCA - Andrian Andrian (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2019)
Now days, The most needed of digital images is influenced by the people will that want to take a part of moment life into digital image. The good digital image has the big filesize, so it will need more space memory to saving more images. There is technique in image processing to decrease file size that is compression. By combine wavelet transformation method and Principal Component Analysis in developing application can produce the good compression technique.